2022
DOI: 10.1111/wre.12528
|View full text |Cite
|
Sign up to set email alerts
|

Time to kill the beast – Importance of taxa, concentration and timing during application of glyphosate to knotweeds

Abstract: Knotweeds (Fallopia spp., syn. Reynoutria spp.) are among the most invasive plants globally, mainly due to their ability to regenerate from rhizomes and their extremely high biomass production. Spraying with glyphosate is a common control method, yet little is known about its effectiveness on underground rhizomes. In addition, there are concerns about the negative environmental impact of glyphosate. Therefore, it is essential to use appropriate dosages and application times to avoid overuse. Based on a pot tri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 31 publications
1
10
0
Order By: Relevance
“…However, an alternative explanation might lie in the potential for better, more complete coverage of the systemic herbicide applied in mid‐summer, simply as a function of reduced canopy area (Boyd et al, 2017). Our data do not allow us to distinguish these two alternatives, but does suggest that optimizing long‐term control of knotweed using sequential contact and systemic herbicide treatments warrants additional testing; ideally, these would include examination of the interactive effects on above and belowground systems (Ito & Ito, 2021; Kadlecová et al, 2022).…”
Section: Discussionmentioning
confidence: 89%
See 4 more Smart Citations
“…However, an alternative explanation might lie in the potential for better, more complete coverage of the systemic herbicide applied in mid‐summer, simply as a function of reduced canopy area (Boyd et al, 2017). Our data do not allow us to distinguish these two alternatives, but does suggest that optimizing long‐term control of knotweed using sequential contact and systemic herbicide treatments warrants additional testing; ideally, these would include examination of the interactive effects on above and belowground systems (Ito & Ito, 2021; Kadlecová et al, 2022).…”
Section: Discussionmentioning
confidence: 89%
“…It is challenging to speculate on the outcome of sequential application of a contact and systemic herbicide applied over several years; dramatic reduction (albeit without full eradication) of aboveground growth seems likely, and remaining stems and leaves might exhibit signs of stress (e.g., light utilization efficiency, Jones et al, 2018). However, eradication of knotweed ultimately demands reduction of rhizome activity and viability (Bashtanova et al, 2009), which have been shown to vary with treatment timing (Kadlecová et al, 2022). We recommend that future studies of sequential applications should include assessment of changes in belowground and aboveground growth (Ito & Ito, 2021; Kadlecová et al, 2022); ideally these would be implemented as long‐term field‐based designs that can help inform management (Jones et al, 2018; Kadlecová et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations